2016
DOI: 10.1016/j.cell.2016.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Neuron-Specific Optogenetic Stimulation in Rhesus Macaques

Abstract: SummaryOptogenetic studies in mice have revealed new relationships between well-defined neurons and brain functions. However, there are currently no means to achieve the same cell-type specificity in monkeys, which possess an expanded behavioral repertoire and closer anatomical homology to humans. Here, we present a resource for cell-type-specific channelrhodopsin expression in Rhesus monkeys and apply this technique to modulate dopamine activity and monkey choice behavior. These data show that two viral vecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
215
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 248 publications
(220 citation statements)
references
References 65 publications
5
215
0
Order By: Relevance
“…This process is thoroughly described in the study by Stauffer et al (2016). Applying photostimulation to the regions found to underlie tremor development and motor dysfunction in MS, such as gait, would be a feasible means of treating these symptoms, given its documented applications in similar cases (Kravitz et al, 2010).…”
Section: Journal Of Young Investigatorsmentioning
confidence: 99%
See 3 more Smart Citations
“…This process is thoroughly described in the study by Stauffer et al (2016). Applying photostimulation to the regions found to underlie tremor development and motor dysfunction in MS, such as gait, would be a feasible means of treating these symptoms, given its documented applications in similar cases (Kravitz et al, 2010).…”
Section: Journal Of Young Investigatorsmentioning
confidence: 99%
“…Celebrating 20 years of undergraduate research (Stauffer et al, 2016;Tønnesen, 2013). This process is thoroughly described in the study by Stauffer et al (2016).…”
Section: Journal Of Young Investigatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, even the development of optogenetic techniques for NHPs in the central nervous system (CNS) has proven challenging with examples of successful viral transduction studies slowly beginning to accumulate [27][28][29][30][31][32][33]. A handful of studies have demonstrated viral transduction of peripheral neuromuscular tissue with fluorescent proteins in NHP models [34,35], but optogenetic modulation of peripheral neural activity in primates similar to the aforementioned rodent studies has not been reported to date.…”
Section: Introductionmentioning
confidence: 99%